(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The goals of physical education lessons at school, which are reflected in the subject standard «Physical education» for grades 5-9 of general education organizations of the Kyrgyz Republic» , are perceived as an example, standard and model for measuring learning outcomes. The article studied which goals, presented in the standard, are preferred by 9-grade students, parents, physical education teachers and future teachers, combined into four groups. Of the 14 goals, the respondents identified the most important and priority 7 goals, which were measured by assessing the frequency repeatability and associated percentages. The obtained results showed that the goals related to knowledge about physical culture are not assessed by a group of students as priority compared to the goals of motor skills development. It is recommended to pay special attention to the development of spiritual values, as well as to knowledge about the healthy lifestyle of students when determining the goals and objectives of physical education lessons, when preparing future teachers, as well as when participating in sports events.